SEROPREVALENCE OF HEPATITIS B IN OUTDOOR FEMALE PATIENTS OF REPRODUCTIVE AGE GROUP AT AYUB TEACHING HOSPITAL ABBOTTABAD - Farid, Jamila; Salim, Taher; Sarwar, Javed; Idris, Muhammad; Gul, Nasreen; Shah, Syed Humayun; Suleman, Muhammad (Journal of Ayub Medical College Abbottabad, 2009)
Background: Hepatitis B is inflammation of the liver caused by a Hepatitis B virus, having a parenteral mode of entry and infecting millions of people around the world. Objective: The present study was planned to assess the seroprevalence of Hepatitis B in women of reproductive age in Hazara in order to promote disease prevention in the perinatal period by vaccination against Hepatitis B. Subjects and Methods: Women 15-45 years old belonging to Hazara Division were included in this descriptive, cross-sectional study conducted over a period of one year at the Department of Microbiology, Ayub Medical College, Abbottabad in collaboration with the Department of Pathology, Ayub Teaching Hospital, Abbottabad from 1st March 2006 to 28th February 2007. Non-probability convenience sampling was done to select 500 females from those visiting Ayub Teaching Hospital Abbottabad as outdoor patients or accompanying person. History, examination, and serum alanine aminotransferase estimation were followed by the initial screening for Hepatitis B surface Antigen (HBsAg) using immunochromatographic device. Enzyme linked Immunosorbent assay was used to confirm the presence of HBsAg. Results: HBsAg was detected in 3% of the women. History of multiple injections was present in 100%, blood transfusion in 22%, dental procedure in 46% and surgical procedure in 43% of the subjects. Only 1% women had been vaccinated. Conclusion: Seroprevalence of the Hepatitis B is not different from the figures reported by the studies previously conducted on general population in Pakistan. However it is different from those reported for the special groups. Keywords. Hepatitis B, Viral Hepatitis, Chronic liver disease, HBsAg, immunochromatographic device, ELISA